In Praise of Tenure: A Cautionary Essay - Merton C. Bernstein (Washington University Law Quarterly, 1993)
Some argue that academic freedom would suffice without tenure. The simple answer is that, if the rules of academic freedom existed alone, those who claim its protection would have the full burden of proving violations. With tenure added, adverse actions against faculty must be justified. Quite apart from burdens of proof, the tradition of faculty intellectual independence has been bolstered by tenure and the protective procedures that accompany it.
Keywords: Academic freedom